1991
DOI: 10.1097/00004032-199102000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Hand Dose Measurements in Interventional Radiology

Abstract: Measurements of radiation dose to the hand were conducted using TLD ring badges for individual interventional radiology cases. Results from over 30 examinations (including transhepatic cholangiograms and biliary and nephrostomy procedures) conducted by four radiologists using identical equipment show an average hand dose of 1.5 mGy (150 mrad) per procedure. Hand dose varied inversely with distance from the patient. Due to variable hand positions during clinical examinations, fluoroscopic time was not found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…This demonstrates that high doses to the extremities do not just occur in exceptional cases. Finger or hand doses of more than 1 mSv have also been published by Felmlee et al [1] and Whitby and Martin [8].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…This demonstrates that high doses to the extremities do not just occur in exceptional cases. Finger or hand doses of more than 1 mSv have also been published by Felmlee et al [1] and Whitby and Martin [8].…”
Section: Discussionmentioning
confidence: 74%
“…Several investigations [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] revealed that the doses to medical staff in interventional radiology and cardiology may be of concern from a radiation hygiene point of view. Partial-body doses reported ranged from a few microsieverts up to a few millisieverts per procedure, with higher values occurring mainly for the hands.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Interventional radiologists have the potential to receive significant radiation doses. 4,5 However, the level of knowledge of radiation risks decreases dramatically outside of the specialist environment of the radiology department with most doctors underestimating the radiation doses associated with a variety of radiological investigations. 6 There are few reports for the radiation risk associated with the use of x-ray usage outside the specialized environment of the radiological department.…”
mentioning
confidence: 99%
“…Despite the fact that, during recent years, a number of efforts have been put into the protection of both patients and staff, information about radiation exposure during ERCP remains scarce. Published work on radiation protection in IR is mainly focussed on various angiographic and cardiological procedures [5][6][7][8][9][10][11][12][13][14][15][16]. Few international papers have been published that evaluate radiation exposure to patients [7,[17][18][19][20] and staff [21][22][23] during ERCP.…”
mentioning
confidence: 99%